Role of cryopreserved multipotent mesenchymal stromal cells in modulation of some indices of cell immunity in adjuvant arthritis - Vvedenskiy, D; Volkova, N; Babenko, N; Gaevska, Yu; Yukhta, M; Goltsev, A. (Reumatologia 2022; 60, 3: 213–219, 2022)
Inroduction: The results of experimental and clinical studies in recent years indicate that the transplantation of multipotent mesenchymal stromal cells (MMSCs) is a possible approach for the “restoration” of the immune system of patients with autoimmune diseases, in particular, rheumatoid arthritis. However, the strength and duration of the effect vary greatly, which indicates incomplete correction of the tested parameters, thereby opening up the prospect of improving this method of treatment by choosing dose-time parameters and methods of their administration. The aim of this research was to determine the indices of cellular immunity in animals with adjuvant arthritis and therapy with cryopreserved MMSCs derived from adipose and cartilage tissues. Material and methods: Adjuvant arthritis in male rats was modeled by subplantar administration of Freund’s complete adjuvant. On day 7 of modeling, experimental animals were administered with saline (control group) or cryopreserved MMSCs from adipose or cartilaginous tissue locally or generalized. On day 28 after therapy the body weight, spleen index and cellularity, and content of CD3+, CD4+, CD8+, CD4+CD25+ cells in the spleen were determined. Results: In the control group of animals, the inflammation was pronounced, as evidenced by a significant increase in the studied parameters throughout the observation period. The use of cryopreserved MMSCs from adipose and cartilaginous tissues led to the restoration of T regulatory cells (Treg) on day 28. Generalized administration of cells had a more pronounced therapeutic effect compared to the animals with local administration. These data can be used to justify and develop a therapeutic approach to rheumatoid arthritis in clinical practice. Conclusions: Cell therapy with cryopreserved MMSCs from investigated sources provided by both local and generalized administration to animals with adjuvant arthritis has a correcting effect on the cellular immunity.
Vvedenskiy D., Volkova N., Babenko N., Gaevska Yu.,Yukhta M., Goltsev A.M. Role of cryopreserved multipotent mesenchymal stromal cells in modulation of some indices of cell immunity in adjuvant arthritis. Reumatologia 2022; 60, 3: 213–219 DOI: https://doi.org/10.5114/reum.2022.117842
Keywords: cell therapy; T cells; adjuvant arthritis; cryopreserved multipotent mesenchymal stromal cells